‘Finding the play’ – exploring with occupational therapists practice possibilities in the context of Irish schoolyards - Michelle Bergin; Bryan Boyle; Margareta Lilja; Maria Prellwitz (Scandinavian Journal of Occupational Therapy)
Background Research has identified diverse constraints to the adoption of school-based occupational therapy approaches and a lack of attention to addressing the barriers to children’s play opportunities. Critical contextualised research is advocated to inform practice possibilities.Aims/Objectives This inquiry aimed to explore with occupational therapists their existing practices in Irish schoolyards to generate practice possibilities concerned with play, as an issue of occupational justice.Materials and Methods Using the theory of practice architectures, six occupational therapists from diverse sites of practice participated in the first phase of a critical action research process using dialogical focus group and occupational mapping methods.Results Three themes were generated (1) Existing practices as situated (2) (Re)mattering play and practices as occupations and (3) Practice possibilities – ‘Finding the play’ between responsiveness and responsibilities. A further interrelated dimension was how the research methods provided mechanisms of raising consciousness.Conclusions, and Significance Alongside constructing knowledges on existing practices in an Irish context, this inquiry contributes to understandings of practices as socially embedded generative processes of ‘finding the play’, highlighting ethical responsibilities to make visible inequities reproduced in habitual practices and engage in relationships of solidarity to (re)construct alternative shared practices.